1986
DOI: 10.1007/bf01534067
|View full text |Cite
|
Sign up to set email alerts
|

Twentieth-century attitudes toward masturbation

Abstract: This article demonstrates the progress that medicine, psychiatry, religion, and anthropology have made toward a variant perspective, of masturbation. Researchers documented the suffering and damage caused by classically ingrained religious and medical distortions.The "secret sin" of Judeo-Christianity and the "social disease" of nineteenth-century medicine has paradoxially become the therapy for various forms of psychosexual dysfunction. Catholic, Protestant, and Jewish denominations polarize opinions from rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 6 publications
0
17
0
1
Order By: Relevance
“…Individual motivation for abstaining from masturbation has been diversely scattered across recent history. It is present in religious arguments, discussions surrounding the fear of physiological or psychological consequences, and efforts to avoid feelings of guilt or loss of control (Patton, 1986). Until the early modern age, moralists and theologians considered masturbation a "sin against nature" (Stolberg, 2000), whereas medical professionals left it largely unnoticed (Laqueur, 2003).…”
Section: Historical Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…Individual motivation for abstaining from masturbation has been diversely scattered across recent history. It is present in religious arguments, discussions surrounding the fear of physiological or psychological consequences, and efforts to avoid feelings of guilt or loss of control (Patton, 1986). Until the early modern age, moralists and theologians considered masturbation a "sin against nature" (Stolberg, 2000), whereas medical professionals left it largely unnoticed (Laqueur, 2003).…”
Section: Historical Perspectivementioning
confidence: 99%
“…In one edition of this work, Tissot (1781) elaborated on the concept of a "post-masturbatory disease." He regarded the loss of semen and the mechanical manipulation of the genitals as possible causes of infection, sexual dysfunction, and insanity (Patton, 1986;Stolberg, 2000). Complementing religious arguments, fear of pathological consequences became an incentive to abstain from masturbation (Kontula & Haavio-Mannila, 2003).…”
Section: Historical Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Although myths surrounding masturbation permeate society, it has become "accepted" as a natural aspect of human sexuality (Patton, 1986). McGaughey and Tewksbury (2002) indicated that ".…”
Section: Autoeroticismmentioning
confidence: 99%